Increased Risk of Second Primary Cancers Following Diagnosis of Malignant Intraductal Papillary Mucinous Neoplasms of the Pancreas: A Population-Based Study - Huang, Xiaoyi; Zhang, Bingbing; Zhao, Jian; Sun, Chen; Kong, Kaiwen; Deng, Lulu; Liu, Yanfang; Zheng, Jianming (Frontiers in Oncology, 2019)
Introduction: Several studies have reported that intraductal papillary mucinous neoplasms (IPMNs) of the pancreas are associated with extra-pancreatic malignancies. However, there have been no population-based studies evaluating the risk of second primary cancers (SPCs) in patients with pancreatic IPMN. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was used to identify and characterize data from patients with IPMN of the pancreas. The standard incidence ratio (SIR) of this cancer was calculated by estimating the relative risk (RR). A multivariate Cox regression model was used to estimate hazards ratios (HRs) of death and associated 95% CIs. Results: Of 2,850 patients with IPMN of the pancreas, 104 patients (3.65%) developed 118 SPCs. The SIR for all SPCs combined was 1.22 (95% confidence interval [CI] = 1.01–1.46; P < 0.05). There was an elevated risk of site-specific SPCs in the small intestine (SIR = 8.68; 95% CI = 2.36–22.22), pancreas (SIR = 2.66; 95% CI = 1.15–5.25), urinary bladder (SIR = 2.02; 95% CI = 1.05–3.54), and eye and orbit (SIR = 13.47; 95% CI = 1.63–48.67) in patients with pancreas IPMN. In age subgrouping, people aged younger than 50 years had an increased risk of all-site SPC with an SIR of 6.44 (95% CI = 2.78–12.68). Cox regression modeling showed that advanced disease stage and a short latency period carried a higher risk of death in IPMN patients with SPC. Conclusions: Patients diagnosed with pancreatic IPMNs were at higher risk than the general population for developing a second primary malignancy. Meanwhile, advanced historic stage and short latency period were associated with an elevated HR in IPMN patients who develop an SPC.